Destabilization of an alpha-helix-bundle protein by helix dipoles. - Gilson, M K (1989)
The finite difference Poisson-Boltzmann method is used to calculate the electrostatic work of assembling the four alpha-helices of Themiste dyscritum hemerythrin to form the protein's observed antiparallel helical bundle. The calculations account for the interaction of each helix dipole with the high-dielectric solvent as well as for pairwise interactions of the dipoles with each other. We find that the electrostatic work of assembly is dominated by unfavorable changes in dipole-solvent interactions rather than by favorable interactions between antiparallel helices. Furthermore, the electrostatic energy difference between the observed arrangement of helices in hemerythrin and at least one other possible helical arrangement is less than 1 kT. These results suggest that the helix dipole actually destabilizes the helical bundle and that it plays little or no role in producing the observed bundle geometry.